2012
DOI: 10.1097/brs.0b013e31822ff5c1
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Risk Factors of Primary Adult Scoliosis Surgery

Abstract: Overall complication rate was 39%, and 26% of the patients were reoperated for mechanical or neurological complications. Risk factors include number of instrumented vertebra, fusion to the sacrum, PSO, and preoperative pelvic tilt of 26° or more. There is a 44% risk of a new operation in the 6-year-period after the primary procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
141
5
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(165 citation statements)
references
References 23 publications
(10 reference statements)
8
141
5
6
Order By: Relevance
“…Radiographic fusion was also achieved in 91%. These results are consistent with other studies on lateral interbody fusion [7][8][9][10][11]. …”
Section: Discussionsupporting
confidence: 83%
“…Radiographic fusion was also achieved in 91%. These results are consistent with other studies on lateral interbody fusion [7][8][9][10][11]. …”
Section: Discussionsupporting
confidence: 83%
“…More recently, a retrospective review of data collected from six centres in France (analysing 306 patients) indicated a 39 % overall complication rate for primary adult scoliosis surgery; 26 % of patients were re-operated for mechanical or neurological complications and the risk of re-intervention resulted to be 44 % in the 6-year period after the primary procedure [14].…”
Section: Discussionmentioning
confidence: 99%
“…One study reported a reoperation rate of 7% for isolated decompression, 15% for short fusion and 28% for long fusion in patients with degenerative lumbar scoliosis 2 years after the index surgery [8]. Charosky et al [11] reported a 44% risk of reoperation after a mean follow-up of 5.8 years in patients that had undergone primary adult scoliosis surgery with a mean of seven instrumented levels. Our figures point in the same direction but were without significant differences between the major and minor surgery groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more follow-up data regarding the risk of repeated surgery after several years is needed [8,11,12].…”
Section: Introductionmentioning
confidence: 99%